2022
DOI: 10.3390/ijerph19031268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Early Phase of COVID-19 on the Autistic Community in Sweden: A Qualitative Multi-Informant Study Linking to ICF

Abstract: While the COVID-19 pandemic is ongoing, early outcome studies indicate severe and pervasive global effects of the pandemic and associated measures to prevent the spread of the virus. General population studies, as well as insight into the outcomes for particular groups, will be necessary in order to mitigate potentially long-term effects as well as to prepare for future epidemics or pandemics. The pandemic conditions have been marked by rapid and abrupt changes and unpredictability which are circumstances that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
6
19
0
Order By: Relevance
“…The stress worsened their well-being and resulted in increased tension and feelings of difficulty in mental functioning. Other studies [ 47 , 48 , 57 , 58 , 59 ] reported similar findings, confirming that increased stress in situations of isolation was experience by many respondents with ASD.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The stress worsened their well-being and resulted in increased tension and feelings of difficulty in mental functioning. Other studies [ 47 , 48 , 57 , 58 , 59 ] reported similar findings, confirming that increased stress in situations of isolation was experience by many respondents with ASD.…”
Section: Discussionsupporting
confidence: 71%
“…Results of his study indicate that both positive and negative consequences can be observed in the psychosocial functioning of people with ASD during the pandemic. The ambiguous impact of lockdown has been confirmed by a number of studies in which individuals with ASD as well as their families indicate both positive effects related to the reduction of social demands and normalization of daily life, as well as a negative impact of the pandemic on their mental health [ 48 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the knowledge of the effects of the COVID-19 pandemic on mental health in the general population is now well established, less is known about its impact on specific and vulnerable populations. This information is particularly important to further enhance the potential to prepare for future epidemics and pandemics, as well as providing targeted intervention and support measures for particularly affected groups, such as children with chronic illness [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that families of children with neurodevelopmental conditions were worried about their child's academic performance and progress during the first COVID-19 school restrictions in 2020 (Hill et al, 2021;Mumbardó-Adam et al, 2021;Tokatly-Latzer et al, 2021;Fridell et al, 2022;Thorell et al, 2022). Indeed, it was estimated that primary schoolaged children in England showed 2 months delay in reading and mathematics due to the COVID-19 school restrictions in 2020 when assessed in autumn 2020 (Leahy et al, 2021;Rose et al, 2021).…”
Section: Introductionmentioning
confidence: 99%